Pengaruh Pertumbuhan Aset, Ukuran, dan Profitabilitas Perusahaan terhadap Penghindaran Pajak (Tax Avoidance) pada Perusahaan Sektor Pertambangan yang Terdaftar di BEI Periode 2017-2020 - Hesty Yana Sari; Evi Yuniarti; Artie Ardhita Rachman (Universitas Widyatama, 2022)
Many companies do tax avoidance because, tax avoidance is an effort to reduce taxes that can be done but still comply with the provisions of applicable tax regulations such as taking advantage of legal loopholes and allowable deductions or delaying taxes that have not been regulated in tax regulations. . This study was conducted with the aim of analyzing the effect of asset growth, size, and company profitability on tax avoidance in mining sector companies listed on the Indonesia Stock Exchange for the 2017-2020 period. The population used in this study is all mining sector companies listed on the Indonesia Stock Exchange for the 2017-2020 period. The technique used by the author in sampling using purposive sampling method, namely the sampling method with certain considerations, in order to obtain 76 research samples based on the criteria. Hypothesis testing using multiple linear regression analysis. The results of the research that have been carried out indicate that it can be concluded that all independent variables simultaneously (together) affect the dependent variable. The partial test results show that asset growth has no effect on tax avoidance, firm size has a significant positive effect on tax avoidance at a significant level of 10%, while profitability with ROA proxy has a significant negative effect on tax avoidance at a significant level. than 5%.